A comment on "Modeling of MOS transistors with nonrectangular gate geometries" - De Mey, G. (IEEE transactions on electron devices, 1983)
In the above mentioned paper, MOS transistors are investigated using the well-known Sah model. It was proved that for a given sheet conductivity law, conformal mapping techniques can be used to treat the nonlinear potential equation. It will be demonstrated that, by introducing an auxiliary potential function, the problem is reduced to the Laplace' equation, for which conformal mapping techniques are obvious. The method is also extended to arbitrary sheet conductivities.